The Impact of Prepartum Depression and Birth Experience on Postpartum Mother-Infant Bonding: A Longitudinal Path Analysis - Eitenmüller, Pia; Köhler, Siegmund; Hirsch, Oliver; Christiansen, Hanna (Frontiers in Psychiatry, 2022)
Introduction: Negative effects of impaired postpartum mother-infant-bonding on mental health of mothers, their newborn children and subsequent child development are well documented. Previous research demonstrated an association between a negative birth experience and postpartum mental health affecting postpartum mother-infant bonding. This study investigates the extent to which prepartum depression and birth experience influence the postpartum mental health of mothers and their bonding towards their newborns, and whether these influences differ according to parity and self-reported prior mental health problems. Method: N = 354 women (18 to 43 years; M = 30.13, SD = 5.10) filled in the the Edinburgh Postnatal Depression Scale (EPDS), the Maternal-Fetal Attachment Scale (MFAS), Salmon’s Item List (SILGer12) assessing the birth experience, and the Postpartum Bonding Questionnaire (PBQ) at pre- and postpartum; they were also asked about birth complications and parity status. Results: Primipara reported significantly more birth complications (p = .048), with path analysis confirming this result (p < .001). Birth complications were associated with a more negative rating of the overall birth experience (p < .001). Mothers with self-reported prior mental health problems had higher prepartum depression scores (p < .001), but did not differ in other variables from mothers without prior self-reported mental health problems. Differences in depression scores between mothers with self-reported prior mental health problems and those without vanished at postpartum assessment (p > .05). Path-analysis highlighted the key role of postpartum depression, which was the only significant predictor of postpartum impairment in maternal-child bonding (p < .001). Birth experience and prepartum depression scores exerted an indirect effect on postpartum maternal-child bonding, mediated by postpartum depression. Discussion: The present study demonstrates the relevance of prepartum mental health of expectant mothers, especially of those who self-report prior mental health problems. The results support that reducing mental health problems of pregnant mothers might contribute to a more positive birth experience and potentially reduce postpartum depressive symptoms. As postpartum depression is associated with impaired parent-child bonding, such targeted interventions could promote child development. Group differences between primiparous and multiparous mothers suggest that the birth experience may be an influential factor for postpartum mental health.